Impact of ESG Scores on Financial Performance: Evidence from Non-Financial Companies Listed on the Indonesia Stock Exchange - Junia, Annisa Aghniarahma; Prasetia, Irsyad Fauzan (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) scores on the financial performance of non-financial sector companies listed on the Indonesia Stock Exchange (IDX). The ESG scores used in this study are obtained from Morningstar Sustainalytics, which provides standardized assessments of ESG risks faced and managed by companies. Financial performance is measured using Return on Assets (ROA) and Tobin’s Q to represent operational performance and market valuation, respectively. This research uses secondary data collected from annual financial reports and Morningstar for the period 2021–2024. The sample is selected through purposive sampling of non-financial companies that have ESG scores on Morningstar and are consistently listed on the IDX. Multiple linear regression analysis is employed to examine the relationship. The results are expected to reveal whether ESG scores significantly influence financial performance, providing insights for investors and management in promoting sustainable business practices.